Business Environment in Nepal - Shrestha, Rajendra Prasad (Economic Journal of Nepal, 2011)
With a view to analyzing the business environment in Nepal, this paper argues that merely formulating and enforcing regulations does not ensue conducive business environment. However they are important for the efficient operation of the market. The excessive compliance costs discourage growth, employment and competitiveness of the firm by diverting energy and resources of the firm from more productive uses. The firm's attention is diverted towards looking at ways and means for the avoidance of regulations. The World Bank reported higher compliance costs in many developing countries. Nepal is not an exception to this. The surveys of manufacturing establishments conducted by Central Bureau of Statistics at different point in time have clearly shown the declining trend of number of establishments and employment in Nepal. One of the main reasons for this is higher compliance costs of regulations. These high compliance costs of regulations are threatening the very survival and growth of enterprises. Key words: Conducive business environment; Employment and competitiveness; survival and growth of enterprises. Economic Journal of Nepal A Quarterly Publication of the Central Department of Economics, Tribhuvan University, Kirtipur, Kathmandu Vol. 30, No.3, July-September 2007 Page :147-161 Uploaded date: 21 July, 2011